2009
DOI: 10.1108/02683940910989002
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of job‐limiting pain and political skill on job satisfaction and organizational citizenship behavior

Abstract: PurposeJob‐limiting pain (JLP) is an increasingly relevant topic in organizations. However, research to date has failed to examine the stress‐inducing properties of pain and its effects on job satisfaction and organizational citizenship behavior (OCB). To address this gap, the purpose of this paper is to examine the interactive relationship between JLP and political skill (PS) on job satisfaction (Studies 1 and 2) and OCB (Study 2).Design/methodology/approachIn the first study, data are gathered from 143 emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 139 publications
(188 reference statements)
1
26
0
Order By: Relevance
“…Studies have shown that an individual characteristic is a vehicle in a political environment and serves as an alternative resource through which other resources are safeguarded from depletion due to job stressors [45]. Moreover, the findings of studies on moderating roles of political skills indicated that employees lacking in political skill are said to be less satisfied [45][46][47]. Thus, we argue that PS weakens the negative association between perception of politics and job satisfaction.…”
Section: Political Skill As a Moderator Of Pop-job Satisfaction Relatmentioning
confidence: 72%
“…Studies have shown that an individual characteristic is a vehicle in a political environment and serves as an alternative resource through which other resources are safeguarded from depletion due to job stressors [45]. Moreover, the findings of studies on moderating roles of political skills indicated that employees lacking in political skill are said to be less satisfied [45][46][47]. Thus, we argue that PS weakens the negative association between perception of politics and job satisfaction.…”
Section: Political Skill As a Moderator Of Pop-job Satisfaction Relatmentioning
confidence: 72%
“…One of the most quantifiable functional impacts of pain among working‐age adults is its toll on occupational performance, career advancement, family income, and competitive employment. Individuals with chronic pain are more likely to receive negative supervisor performance ratings (Kessler et al., ), feel dissatisfied or disengaged from their work (Ferris, Rogers, Blass, & Hochwarter, ), experience more sick days (Patel et al., ), and exit the job market prematurely (Langley et al., ). Low back and neck pain are among the five leading causes of Disability Adjusted Life Years worldwide (Murray et al., ), and the Institute of Medicine estimates an annual disability cost of chronic pain in the US between $560 and $635 billion, 30% higher than the combined cost of cancer and diabetes (Gaskin & Richard, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, persuasive behavior is more likely to occur among people with good quality interpersonal relationships. On the other hand, current government regulations and the overall social atmosphere are promoting approved environmentally friendly behavior (Ferris et al, 2009) [49]. Thus, under the influence of group norms, individuals worried that they might create bad impressions will carry out disposal behavior in order to maintain a good relationship with other groups and meet social expectations.…”
Section: Differences In Individual Demographic Characteristics Of Parmentioning
confidence: 99%